Interactions among national and supranational identities: mobilizing the independence movement in Scotland - Heaney, Michael T.; Anderson, Erika L.; Cancro, Madilyn E.; Martin, Grace E. (Frontiers in Political Science, 2023)
As nationalism rises worldwide, understanding the relevance of national identities is at a premium in both the study of mass political behavior and the analysis of social movements. Drawing on research in social psychology, this study explores interactions among national and supranational identities using the concepts of identity interference (i.e., negative interactions) and identity complementarity (i.e., positive interactions). These interactions extend beyond the direct effects of identity considered in many previous studies. Focusing on interactions centers the analysis on the contextual aspects of identity during nationalist mobilizations. Survey data from Scotland demonstrate that interactions among Scottish, British, and European identities were consequential for mobilizing support for Scottish independence in 2019. Strong evidence indicates interference between Scottish and British identities. European and Scottish identities complement one another among independence supporters but not in the general population. The possibility of interference between European and British identities is backed by only mixed results. The timing of this study in the aftermath of the Brexit referendum was likely relevant to its findings on European identity. Overall, this research illustrates the benefits of widening the empirical examination of multiple identities in the social sciences.